Evaluation of Azadirachta indica as a Soil Amendment for Controlling Bacterial Wilt of Tomato - Chalida Leksomboon (Agriculture and Natural Resources, 2009)
Azadirachta indica A.Juss. (Neem) was evaluated as a possible alternative to soil treatment under greenhouse conditions, for the control of bacterial wilt in tomato plants caused by Ralstonia solanacearum. Thirty-day-old tomato seedlings were planted in 10-inch plastic pots that had been filled with infested soil amended by 5% crushed neem seed. The wilting symptom percentage of plants was determined weekly. The inclusion of the crushed neem seed in the soil significantly reduced the incidence of bacterial wilt on the susceptible cultivar, Seedathip3. Disease incidence in the untreated, infested soil (control) reached 100%, while in the neem-treated samples only 50% disease incidence occurred. Neem affected the bacterial count of R. solanacearum in the soil at 28 and 56 days after planting (DAP). Populations of R. solanacearum decreased at 28 DAP and no bacteria were detected in the neem treatment at 56 DAP. The observed reduction in the pathogen population and the increase in healthy plants in the greenhouse indicated that neem could have an important role in biologically based management strategies for the control of bacterial wilt disease.